2021
DOI: 10.17509/ijert.v1i1.33367
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the Google Meet and Quiziz Applications in the Assistance and Strengthening Process of Online Learning during the COVID-19 Pandemic

Abstract: The current Covid-19 pandemic has an impact on all fields including education. One of them is basic education, which requires teachers for online learning. The research objective is to fulfill the thematic student study service task regarding the Prevention and Management of the Impact of Covid-19 in the field of education. At this time, all learning in Indonesia is being pursued online so that there is minimal interaction. Therefore, this study aims to determine the effectiveness of online learning that takes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 7 publications
1
26
0
9
Order By: Relevance
“…In Nasution et al's (2021) study, they aimed to fulfil the task of distance education and student study service related to the prevention and management of the effect of COVID-19 in the field of education; as a result, they found that Internet infrastructures are good and online-based learning tends to be effective and works without any problems. Based on the relevant researches in this context, it can be seen that distance education systems get good results if they are used correctly in education [9].…”
Section: Related Studiesmentioning
confidence: 99%
“…In Nasution et al's (2021) study, they aimed to fulfil the task of distance education and student study service related to the prevention and management of the effect of COVID-19 in the field of education; as a result, they found that Internet infrastructures are good and online-based learning tends to be effective and works without any problems. Based on the relevant researches in this context, it can be seen that distance education systems get good results if they are used correctly in education [9].…”
Section: Related Studiesmentioning
confidence: 99%
“…The result of the research obtained that learning by using Google Meet has a positive impact on the students interest because it so convenience to use, flexible, and can be implemented everywhere [26]. Nasution (2021) stated that the online learning tend to get positive result by using google meet and quizziz [15], [27].Many teachers also held online learning asynchronously using WhatsApp and LMS such as Google Classroom and Edmodo. Most of the teacher used WhatsApp to support their online learning.…”
Section: Kind Of Content Used By Teacher To Present Online Learningmentioning
confidence: 99%
“…Hal ini karena Google Meet mudah diimplementasikan, waktu belajar fleksibel dan dapat memfasilitasi proses belajar mengajar walaupun mahasiswa dan dosen berada pada lokasi yang berbeda (Septantiningryas et al, 2021). Kelebihan selanjutnya adalah dapat meningkatkan motivasi belajar (Putra, 2021), dan pembelajaran berjalan dengan efektif dan lancar (Nasution et al, 2021).…”
Section: Muhammad Syazali Dkk 96unclassified